2016
DOI: 10.1371/journal.ppat.1005819
|View full text |Cite
|
Sign up to set email alerts
|

The Strange Lifestyle of Multipartite Viruses

Abstract: Multipartite viruses have one of the most puzzling genetic organizations found in living organisms. These viruses have several genome segments, each containing only a part of the genetic information, and each individually encapsidated into a separate virus particle. While countless studies on molecular and cellular mechanisms of the infection cycle of multipartite viruses are available, just as for other virus types, very seldom is their lifestyle questioned at the viral system level. Moreover, the rare availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 103 publications
0
136
1
Order By: Relevance
“…Variation in gene expression potential at the population level may also facilitate selective regulation of viral gene expression through gene dosing effects, as has been demonstrated for multipartite plant viruses (104,105). Changes in the percentage of particles that carry a functional copy of a given IAV genome segment will alter the stoichiometry of gene segments delivered to multiply infected cells.…”
Section: Effects Of Sips On Population-level Phenotypesmentioning
confidence: 99%
“…Variation in gene expression potential at the population level may also facilitate selective regulation of viral gene expression through gene dosing effects, as has been demonstrated for multipartite plant viruses (104,105). Changes in the percentage of particles that carry a functional copy of a given IAV genome segment will alter the stoichiometry of gene segments delivered to multiply infected cells.…”
Section: Effects Of Sips On Population-level Phenotypesmentioning
confidence: 99%
“…A recent study showed that these different genomic segments consistently accumulate at different relative frequencies in the host plant, defining the genome formula (28). It has been hypothesized that the genome formula could correspond to a gene expression regulation system through the modification of the gene copy number (29). The multipartite structure of the FBNSV genome, the fact that its segments are of similar sizes and share common sequences, and the obvious importance of the genome formula make FBNSV a great model to investigate potential quantitative NGS biases at the intraspecific level.…”
Section: Importancementioning
confidence: 99%
“…These viruses, first described in the 1960s [1], have a genome segmented in two or more parts. According to current evidence, the segments are encapsidated separately and, apparently, propagate independently [2,3]. As of today, there is no mainstream theory able to explain the adaptive advantage of such a strange lifestyle [4].…”
Section: Introductionmentioning
confidence: 99%